Recent advances on bio-based isobutanol separation. (June 2021) - Fu, Chuhan; Li, Zhuoxi; Jia, Chuhua; Zhang, Wanli; Zhang, Yulei; Yi, Conghua; Xie, Shaoqu
Abstract: Bio-based isobutanol has attracted more and more attention due to its wide application and excellent fuel performance. Compared with ethanol, isobutanol has higher energy density, lower oxygen content, and hygroscopicity, making it an ideal gasoline additive or substitute. Bio-based isobutanol has been commercially produced from a variety of renewable feedstock, including corn, wheat, sorghum, barley, and sugar cane by using a yeast biocatalyst. The existing facility of ethanol plants is acquired to separate and purify isobutanol from the fermentation broth, meaning that the energy-intensive distillation process still cannot be replaced. There are still some challenges in the production of bio-based isobutanol, such as low product concentration, unexpected impurities, high separation cost, thus the development of an efficient and low-cost downstream separation process has become one of the keys to the industrial production of bio-based isobutanol. The separation methods for isobutanol recovery, including vacuum evaporation, adsorption, pervaporation, gas stripping, solvent extraction, salting-out, salting-out extraction, are summarized in this review. An outlook on the challenges and opportunities of isobutanol separation is also described in this review.